Strategic Management Accounting for Village-Owned Enterprises in Indonesia - SRIYONO, SRIYONO; SOEPRAPTO, ADI; NUGROHO, SIMON PULUNG; SIRAIT, AFNI (Journal of International Conference Proceedings, 2022)
The growth and development of Village Owned Enterprises in Indonesia is very rapid, but it has not been able to contribute to optimally increasing the income and welfare of rural communities. Strategic management accounting is an approach to management accounting techniques that can support the achievement of organizational goals and objectives. This research is based on contingency theory that there isn’t universally applicable approach. The development of strategic management accounting needs to consider the characteristics of the organization, including the organizational environment. The object of this research is Village Owned Enterprises in Indonesia. Respondents in this study were: administrators (managers) of Village-Owned Enterprises in Indonesia. The data analysis technique used a qualitative description. The results show that most village-owned enterprises in Indonesia have always and often applied strategic management accounting techniques, however, there are still many Village Owned Enterprises  managers who sometimes even rarely apply strategic management accounting techniques. This condition may be one of the factors that not yet optimal function and role of Village Owned Enterprises  in encouraging economic improvement and community welfare. Keywords: Village Owned Enterprises , Strategic Management Accounting